[Subḥat al-abrār, 981, i.e. 1573]. - Jāmī; Muḥammad ibn Mullā Mīr al-Ustādī (Edge title (tail):سبحة الابرار, 1573)
Elegant copy of Subḥat al-abrār, the fourth of the seven seven mas̲navīs of Jāmī (d.1492) collected under the title Haft awrang.
Shelfmark: Ann Arbor, University of Michigan, Special Collections Research Center, Isl. Ms. 330
Origin: As appears in colophon on p.261, copied by Muḥammad ibn Mullā Mīr al-Ustādī [?] with transcription completed 10 Rabīʻ II 981 [ca. 9 August 1573].
Former shelfmark: "179 T. De M. [i.e. Tammaro De Marinis]" inscribed in pencil on recto of front flyleaf / 'title page' (now affixed to each other, p.1) ; ٩٥١ on tail edge of text block.
Binding: Pasteboards covered in quite dark brown (to black) leather with dark red-brown leather repairs to spine and fore edge flap ; Type II binding (with flap) ; doublures in dark red leather with central mandorla, pendants and cornerpieces in filigree appliqué over blue paper and green silk as well as tooled border ; upper and lower covers carry stamped and gold-painted mandorla (filled with vegetal composition reminiscent of Déroche class. OSd 2) with pendants, cornerpieces and a series of bordering lozenges as well as a tooled border ; design continues on flap ; sewn in dull pink thread, two stations ; worked chevron endbands in dull pink and pale green [?], fair condition ; overall in fairly good condition with much abrasion, staining, lifting of leather, etc. ; housed in box for protection.
Support: non-European (likely Persian) laid paper with 8 laid lines per cm. (mainly vertical) and occasional pairs of chain lines faintly visible, dense and sturdy, quite heavily sized and burnished ; written area mounted in tinted leaves (mainly pink except for pp.134-144 where tinted pale orange or peach) ; some breakthrough at frames.
Keywords: Manuscripts, Persian / Michigan / Ann Arbor.; Masnavis, Persian / Early works to 1800; Persian poetry / 747-1500 / http://id.loc.gov/authorities/subjects/sh85100085; Headpieces (layout features) / 16th century. / aat